DETERMINAN EFISIENSI DAN DAMPAKNYA TERHADAP KINERJA PROFITABILITAS INDUSTRI PERBANKAN DI INDONESIA - Subandi, Subandi; Ghozali, Imam (University of Merdeka Malang, 2013)
The objective of this study was to estimate the factors influencing the level of technical efficiency of banksmeasured by a non-parametric Data Envelopment Analysis (DEA) and its impact on the profitability performanceas measured by return on assets (ROA). This study applied panel data regression models with randomeffects approach to 110 conventional bank over 2006-2010. Based on estimation of the determinants of bankefficiency levels, it could be informed that bank size factors, types of banks, capital adequacy ratio, loansdeposit ratio, operating expenses and net interest margin affected the level of technical efficiency significantly.At a later stage, estimation of the determinants of profitability showed that the factors like the bank size, typesof banks, non-performing loans, loans deposit ratio, operating expenses and net interest margin significantlyaffected ROA. This study had implications both theoretically and managerially. Theoretical implications forthis research provided an important contribution to the development of the theory of efficiency and financialperformance. Finnaly the managerial implications of this research had the consequences of improving theefficiency and profitability performance, especially for the domestic banks.